BMSCs-laden gelatin/sodium alginate/carboxymethyl chitosan hydrogel for 3D bioprinting. Issue 110 (15th November 2016) - Huang, Jie; Fu, Han; Wang, Zhiying; Meng, Qingyuan; Liu, Sumei; Wang, Heran; Zheng, Xiongfei; Dai, Jianwu; Zhang, Zhijun
Abstract : Gelatin/sodium alginate/carboxymethyl chitosan hydrogel mixed with bone mesenchymal stem cells for 3D bioprinting. Abstract : Three-dimensional (3D) bioprinting technology offers the possibility to deliver, in a defined and organized manner, scaffolding materials and living cells, and therefore holds much promise for tissue engineering and regenerative medicine. In this work, we explored the possibility of gelatin/sodium alginate/carboxymethyl chitosan (Gel/SA/CMCS) hydrogel combining with bone mesenchymal stem cells (BMSCs) for 3D bioprinting. Compared to the commonly used 3D bioprinting materials such as gelatin/sodium alginate (Gel/SA) hydrogel, the Gel/SA/CMCS hydrogel we developed shows excellent equilibrium water content, good mechanical properties, antibacterial activity, and a slow degradation rate. With this kind of material, we generated a scaffold with homogenous cell distribution. Cell viability after 3D printing showed that over 85% of the printed cells were viable at 0 and 2 days of culturing. Our work demonstrates the feasibility of mixing Gel/SA/CMCS hydrogel with stem cells for 3D bioprinting.